Politeness in Digital Interaction: A Pragmatic Analysis in Genshin Impact Discord Chats - Amelia, Virna; Utami, Silvia; Maspufah, Maspufah (Huele: Journal of Applied Linguistics, Literature and Culture, 2025)
Politeness plays a key role in maintaining smooth communication, especially in chat rooms where tone and intent can be easily misunderstood. This research aimed to identify politeness strategies in Genshin Impact players' messages on the Discord server and identify factors influencing their use by adopting (Brown & Levinson, 1987) theory. This research analyzed chat transcripts from various players in the Genshin Impact Discord server by using a descriptive qualitative method. The findings revealed 113 total utterances that occurred in the politeness strategies: 15 of bald on-record, 65 of positive politeness, 21 of negative politeness, and 12 of off-record politeness. Positive politeness strategies were mostly used in the discord to maintain the close relationship between players. Two main factors that influence politeness in Discord were payoffs (priori consideration) and circumstances of sociological variables. These findings highlight the importance of understanding politeness strategies in shaping respectful and effective communication in online gaming communities.